Causes of removal of the eye In Ibadan (1996)
The aim of the study was to enumerate the causes of removal of the eye in our community and find out ways of reducing this. 139 eyes were removed at the University College Hospital, lbadan, over a 5 year period between January 1989 and December 1993. Only 100 of the cases were available for inclusion in this study. The age, sex, causes of removal of the eyes and final diagnosis were obtained. Most of the patients (64%) were below the age of 30 years, the youngest being 3 weeks of age. The most common cause of eye removal was found to be infective (endophthalmitis/panophthalmitis), although in the age group of 0-10 years, Retinoblastoma was the commonest cause of the removal of the eye.